The dominant invading paths of extreme cold surges and the invasion probabilities in China - Ting Ding; Hui Gao; Yuan Yuan (Atmospheric Science Letters, 2020)
Abstract Based on daily temperature observation dataset with high quality and spatial resolution, this paper revealed the dominant invading paths of the extreme cold surges (ECSs) within China by using the fifth percentile of temperature drops instead of the traditional unified threshold in the operation. The maximal probabilities of the ECSs from the upstream regions to the down‐stream regions along the invading paths are also provided. Results indicate the distribution of the fifth percentile is quite different in various regions, with the highest value centers of more than 8°C in northern China, and a secondary center of 6–7°C in southern China. While in the areas between the Yellow River basin and the Yangtze River basin, the two longest rivers in China, the values are below 5°C. This result explains the unreasonable frequency gap between the two rivers in previous unified threshold. Based on the distribution, the whole country is roughly divided into 18 regions at an approximate box of 5°N × 10°E to acquire clear and objective invading paths by the lead–lag correlation analysis and an objective identification of the paths. Results show the ECS invading path in northern China has a dominant west or northwest track. But in southern China, the invading paths are more complex, generally from north to south. In China, about 30–40% ECS cases in the upstream regions can lead to the ECSs in the down‐stream regions along the dominant paths. By the identification and the lead–lag correlation, northwestern China could be regarded as the source of ECSs invading other regions.